STUDYING THE EFFECT OF INSTITUTIONAL PRESSURES ON THE INTENTION TO ADOPT GREEN INFORMATION TECHNOLOGY: ENVIRONMENTAL AWARENESS AS THE MEDIATING VARIABLE (American Journal of Business Management, Economics and Banking, 2022)
These days, increasing amounts of carbon footprint which is generated by small enterprises at Thi-Qar province pose negative effects to the environment. Consequently, the pressures on these enterprises are escalating. Therefore, the objective of this research is to understand the effect of institutional pressures on the intention managers of these enterprises to adopt green information technology. A research model has been developed to link three components, coercive pressure, normative influence, mimicry, and study the effect of these variables on the intention to adopt green information technology, then exam role of environmental awareness as mediate variable.